Pengaruh Model Pembelajaran Berbasis Masalah Berbantuan Geogebra Terhadap Kemampuan Berpikir Kreatif - Hidayatsyah Hidayatsyah; Nur Elisyah; Amam Taufiq Hidayat; Desy Sary Ayunda (FKIP Universitas Palangka Raya, 2023)
Students low creative thinking abilities can result in students experiencing difficulty in solving mathematical problems. In this study, the researcher aims to find out whether there is an influence of the Geogebra rock problem-based learning model on students' critical thinking abilities. Quasi-experiment is the research method used in this research. Where, there are two classes, namely the experimental class and the control class, namely class VIII-5 and class VIII-6 at SMPIT Al Jawahir, each with 30 students. After this research was carried out, the average final test result for creative thinking ability in the experimental class was 69.10, while the average final test result for creative thinking ability in the control class was 63.20. So it can be concluded that there is an influence between the problem-based learning model assisted by Geogebra on creative thinking skills.